Risk Factors that Affecting Hypertension Incident Among Adult & Elderly in Tambaksari, Surabaya. - Putri, Linta Meyla; Mamesah, Marline Merke; Iswati, Iswati; Sulistyana, Caturia Sasti (Journal of Health Management Research, 2023)
Background: Surabaya city has a high rate of hypertension, one of the region which has highest incidents of hypertension is Rangkah, Tambaksari. The number of hypertension incidents in Tambaksari placed 5th ranks of region which has largest hypertension incidents. Aims: The aim of this study is to analyze the risk factors for hypertension in Rangkah Village, Tambaksari District, Surabaya City Methods: Discriptive analytical research using cross sectional approach. The sample in this study were 44 respondents. Results: The majority of respondents who were at high risk of hypertension are women (60%), pre-adult age group (46%), have primary school education (36.2%), have jobs in the private sector (46%) with the majority of income > IDR. 2,000,000,- . There were significant relationship between nutritional status (p-value= 0.000; OR=3.097), physical activities (p-value= 0.031, OR=1.582), large coffee consumption (p-value= 0.037, OR=1.537), and stress (p-value = 0.031, OR = 1.582) with the risk of hypertension in the Rangkah area, Tambaksari, Surabaya City. Conclusion: There were significant relationship between nutritional status, physical activities, heavy coffee consumption and stress with the risk of hypertension in the Rangkah area, Tambaksari, Surabaya City.